2006
DOI: 10.1038/oby.2006.28
|View full text |Cite
|
Sign up to set email alerts
|

Consequence of Omitting or Adding a Meal in Man on Body Composition, Food Intake, and Metabolism

Abstract: CHAPELOT, DIDIER, CORINNE MARMONIER, ROBERTE AUBERT, CHLOÉ ALLÈ GRE, NICOLAS GAUSSERES, MARC FANTINO, AND JEANINE LOUIS-SYLVESTRE. Consequence of omitting or adding a meal in man on body composition, food intake, and metabolism. Obesity. 2006;14:215-227. Objective: To investigate in man the consequence on body composition and related biological and metabolic parameters of omitting or adding a meal. Research Methods and Procedures: Twenty-four young normal-weight male subjects were recruited, 12 usual fourmeal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 61 publications
(80 reference statements)
1
67
0
2
Order By: Relevance
“…Behaviors of concern most frequently employed by participants in this sample were skipping meals and exercising more than usual. Skipping meals, which leads to within-day energy deficits, can contribute to higher body fat levels 25 and may be particularly problematic for athletes because of their high energy demands during certain periods of the day. 26 Of equal concern, using excessive exercise to increase energy expenditure represents a potentially deleterious strategy to reduce body weight in athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Behaviors of concern most frequently employed by participants in this sample were skipping meals and exercising more than usual. Skipping meals, which leads to within-day energy deficits, can contribute to higher body fat levels 25 and may be particularly problematic for athletes because of their high energy demands during certain periods of the day. 26 Of equal concern, using excessive exercise to increase energy expenditure represents a potentially deleterious strategy to reduce body weight in athletes.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy young men, habitual meal frequency appeared to be of greater significance in energy-intake regulation than forced meal frequency (117)(118)(119)(120) . Adiposity may increase when young lean male subjects switch from a four-to a three-meal pattern by removing their usual afternoon meal, partly mediated by a change in the macronutrient composition of the diet (121) . Assessment of the effect of omitting or adding the third meal, revealing that eating three meals compared with two meals had no effects on 24 h energy expenditure, diet-induced thermogenesis, activity-induced energy expenditure and sleeping metabolic rate.…”
Section: Circadian Misalignment and Sleepmentioning
confidence: 99%
“…23,24) Increased fat mass and respiratory quotient have been suggested to be another hypothesis which is a ributable to gorging pa ern of diets. 25,26) Chapelot et al 26) suggested that body fat and respiratory quotient were increased in subjects who were used to eating four meals per day switched to three meals per day for 4 weeks in 24 men.…”
Section: Korean J Fam Medmentioning
confidence: 99%
“…Breakfast skipping can lead to overeating later in the day for example, having one big meal in the evening, 27,28) as well as e ect of consuming different macronutrient composition of the diet. 26) Besides, omi ing breakfast showed the feature of decreasing eating frequency. 7) Skipping at least one meal a day might be an extreme example of the big maximum meal calorie variation.…”
Section: Korean J Fam Medmentioning
confidence: 99%